2011
DOI: 10.1039/c1nr10539f
|View full text |Cite
|
Sign up to set email alerts
|

Nb doped TiO2 nanotubes for enhanced photoelectrochemical water-splitting

Abstract: Nanostructured titanium dioxide is one of the classic materials for photoelectrochemical water splitting. In the present work we dope TiO(2) nanotube anodes. For this, various low concentration bulk-Nb-doped TiO(2) nanotube layers were grown by self-organizing anodization of Ti-Nb alloys. At Nb-contents around 0.1 at%, and after an adequate heat-treatment, a strongly increased and stable photoelectrochemical water-splitting rate is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
139
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(146 citation statements)
references
References 45 publications
(54 reference statements)
5
139
1
1
Order By: Relevance
“…The plots of the photocurrent as a function of the TiO2 NT length and diameter, These results are in very good agreement with previous published works. 9 It is also worth mentioning that the transient photocurrent curves obtained with the longest tubes exhibited a decay after illumination (Inset of Figure 6a), this can be attributed to an increased recombination over longer transport pathways. The experiment demonstrates the feasibility to use these gradients for the fast screening of tube properties over a wide range of dimensions.…”
Section: Photocurrent Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…The plots of the photocurrent as a function of the TiO2 NT length and diameter, These results are in very good agreement with previous published works. 9 It is also worth mentioning that the transient photocurrent curves obtained with the longest tubes exhibited a decay after illumination (Inset of Figure 6a), this can be attributed to an increased recombination over longer transport pathways. The experiment demonstrates the feasibility to use these gradients for the fast screening of tube properties over a wide range of dimensions.…”
Section: Photocurrent Screeningmentioning
confidence: 99%
“…7,8 The performance of the nanotubes in all these applications depends strongly on their length, diameter and ordering. For instance, an optimal length of 7 m for TiO 2 nanotubes has been reported for solar photoelectrochemical water splitting, 9 ranges of 15-optimum for DSSCs, 4 and it has been shown that TiO 2 nanotubes with a diameter larger than 50 nm impaired the spreading and adhesion of mesenchymal stem cells on nanotubular surfaces. 7,10 Screening the properties of TiO 2 NT arrays as a function of the tubes characteristic dimensions for a given application is consequently of significant importance for the development and the optimization of many important TiO 2 NT-based devices.…”
Section: Introductionmentioning
confidence: 99%
“…Photoelectrochemical water splitting experiments were carried out under simulated sunlight condition AM 1.5 (100 mW/cm²) in 1 M KOH solution as described in Ref [16]. and an annealed nanosponge.…”
Section: Methodsmentioning
confidence: 99%
“…A particularly advantageous method to dope TiO 2 NTs is to anodize alloys of Ti-X (X = W, Mo, Nb), [116][117][118] nanotubes which exhibited similar high conductivity and found that TiO 2 doped with 0.1 at% Nb at an optimal length of 7 μm could produce up to 1.0 mA/cm 2 of photocurrent. 125 In both sets of studies above, the introduction of large amounts of Nb or Ta had detrimental effects, leading the authors to suggest that these elements act as recombination centers at concentrations greater than the optimal concentration of 0.1 at% for both Ta and Nb.…”
Section: Tio 2 Photoanodes In Photoelectrochemical Applications: Modimentioning
confidence: 99%